Major depression as a predictor of the intergenerational transmission of attachment security: Findings from a pregnancy cohort study. (August 2022) - Galbally, Megan; Watson, Stuart J; Tharner, Anne; Luijk, Maartje; Blankley, Gaynor; MacMillan, Kelli K; Power, Josephine; Lewis, Andrew J
Objective: Understanding the relationship between attachment and mental health has an important role in informing management of perinatal mental disorders and for infant mental health. It has been suggested that experiences of attachment are transmitted from one generation to the next. Maternal sensitivity has been proposed as a mediator, although findings have not been as strong as hypothesised. A meta-analysis suggested that this intergenerational transmission of attachment may vary across populations with lower concordance between parent and infant attachment classifications in clinical compared to community samples. However, no previous study has examined major depression and adult attachment in pregnancy as predictors of infant–parent attachment classification at 12 months postpartum. Methods: Data were obtained on 52 first-time mothers recruited in early pregnancy, which included 22 women who met diagnostic criteria for current major depression using the Structured Clinical Interview for the Diagnostic and Statistical Manual of Mental Disorders . The Adult Attachment Interview was also administered before 20 weeks of pregnancy. A history of early trauma was measured using the Childhood Trauma Questionnaire and maternal sensitivity was measured at 6 months postpartum using the observational measure of the Emotional Availability Scales. Infant–parent attachment was measured using the Strange Situation Procedure at 12 months. Results: Overall, we found no significant association between the Adult Attachment Interview and the Strange Situation Procedure classifications. However, a combination of maternal non-autonomous attachment on the Adult Attachment Interview and major depression was a significant predictor of insecure attachment on the Strange Situation Procedure. We did not find that maternal sensitivity mediated parental and infant attachment security in this sample. Conclusion: While previous meta-analyses identified lower concordance in clinical samples, our findings suggest women with major depression and non-autonomous attachment have a greater concordance with insecure attachment on the Strange Situation Procedure. These findings can guide future research and suggest a focus on depression in pregnancy may be important for subsequent infant attachment.